2017
DOI: 10.21577/0103-5053.20170141
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Anti-Inflammatory and Anti-Hypertensive Drugs as Inhibitors of Bacterial Diguanylate Cyclases

Abstract: Biofilms are widely present in many human chronic infections, often more resistant to treatment with antibiotics. Bacterial diguanylate cyclases (DGCs) synthesize cyclic dimeric guanosine monophosphate (c-di-GMP) from two guanosine-5'-triphosphate (GTP) molecules. c-di-GMP is a central second messenger controlling biofilm formation, turning this class of enzymes an attractive target to prevent and disrupt biofilms of pathogenic bacteria. Here, we apply an in silico ligand-and target-based hybrid method to scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…5 For example, Wiggers et al demonstrated that while sulfasalazine inhibited bacterial diguanylate cyclase inhibitor, its two structurally related molecules sulfadiazine and sulfathiazole did not. 6 Notably, current structure-activity studies are based on single strains of bacteria. The human gut microbiome is composed of different bacteria, and the composition of the gut microbiome is different between individuals.…”
Section: Introductionmentioning
confidence: 99%
“…5 For example, Wiggers et al demonstrated that while sulfasalazine inhibited bacterial diguanylate cyclase inhibitor, its two structurally related molecules sulfadiazine and sulfathiazole did not. 6 Notably, current structure-activity studies are based on single strains of bacteria. The human gut microbiome is composed of different bacteria, and the composition of the gut microbiome is different between individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The big difference between the IC 50 values of eprosartan for the different DGCs indicates that not only the key conserved residues interacting with the substrate GTP in DGCs but also different A-site peripheral residues should be considered for designing a virtual inhibitor screening to discover inhibitors with a broad DGC spectrum. Both compounds reduce aggregation of E. coli in the culture broth, suggesting that these two chemicals have anti-biofilm property in vivo (Wiggers et al, 2018).…”
Section: Sulfasalazine and Eprosartanmentioning
confidence: 97%
“…Recently, Wiggers et al screened 1500 FDA-approved drugs in the DrugBank database through a virtual screening method to find competitive inhibitors binding to the A-site of the DGC, C. crescentus PleD (Wiggers et al, 2018). The authors used the combination of the molecular docking strategy and ligandbased methods.…”
Section: Sulfasalazine and Eprosartanmentioning
confidence: 99%